The Effect of Zbxz23ir-21 NANO(nanomaterials) Delivery Vector on Apoptosis and PTEN(phosphatase and tensin homolog deleted on chromosome ten)/PI3K(Intracellular phosphatidylinositol kinase)/AKT(related to the A and C kinase) in Children with CHOLESTEATOMA in Middle Ear. Issue 1 (1st January 2021) - Zheng, Hongwei; Wang, Wenlun; Li, Shichang; Han, Lin
ABSTRACT: Cholesteatoma of the middle ear is a kind of cystic disease with clear boundary formed by the abnormal growth of keratosquamous epithelium in temporal bone. Cholesteatoma otitis caused by it is a common disease in otorhinolaryngology. The EPR effect promotes the selective distribution of macromolecular substances in tumor tissues, which can increase drug efficacy. The purpose of this paper is to prepare and deliver the mir34a small molecule regulator, rubine, by nanotechnology, and to deliver it to the cells successfully. It can passively target tumor tissue through EPR effect, and play its regulatory role on miR-34a, thus inhibiting the growth of cholesteatoma cells. The effects of nano delivery on apoptosis and PIEN/P13K/AKt of children with middle ear choledochoma were tested in this paper. The experimental results were conducted on cholesteatoma cells as cell lines and balb/c nude mice as experimental objects. The expression of PTEN/PI3K/AKT in experimental group and control group was detected by immunohistochemistry. Apoptosis was discussed by cell activity detection. The physical and chemical properties, encapsulation efficiency, drug release ability in vitro and antitumor activity of nanoparticles in vitro and in vivo were studied. The results of cell level experiments in vitro showed that free RUBINE caused about 15% apoptosis, which was not different from RC NPs. The results showed that the nanoparticles could improve the expression of miR-34 in the cells, and then regulate the expression of Bcl-2, Cdk6 and CyclinD1, and play the inhibitory effect of miR-34a on the proliferation and migration of tumor cells.